Dental caries experience and association to risk indicators of remote rural populations - SEAN L. COOK, E. ANGELES MARTINEZ-MIER, (IAPD and Blackwell, 2008)
Dental caries continues to be the most common infectious disease of childhood ; however, this infectious disease process is no longer pandemic, but rather endemic in specific sectors of populations